GAMBARAN PROGRESIVITAS MIOPIA PADA SISWA SMAN 1 BENGKULU SELATAN SELAMA PANDEMI COVID-19 TAHUN 2020-2022 - Afifah Sulaksana (2022)
Myopia is a disorder characterized by difficulty seeing objects. Online learning implementation that requires students to use electronic devices to support learning during the COVID-19 pandemic can cause vision problems. This study aims to get an overview of the progressivity of myopia and the factors that influence myopia progressivity among students of South Bengkulu SMAN 1 during the COVID-19 pandemic. This is a quantitative study using a cross-sectional design. Data were taken using a total sampling technique from 47 students who were using minus glasses and had no history of eye injury or eye surgery. The result of this study showed that during the COVID-19 pandemic, 21.3% of students experienced >0.50-1.75D progressivity of myopia in the right eye, and 19.1% of students experienced >0.50-1.5D progressivity of myopia in the left eye. The Chi-square test showed that the initial age using minus glasses was related to the progressivity of myopia (p = 0.001; OR = 15,750; 95% CI = 2.815-88.123). Other individual and environment factors are not affecting the progressivity of myopia